An Azide-Functionalized Nitronyl Nitroxide Radical: Synthesis, Characterization and Staudinger–Bertozzi Ligation Reactivity - Barbon, Stephanie M.; Gobbo, Pierangelo; Luo, Wilson; Price, Jacquelyn T.; Biesinger, Mark C.; Workentin, Mark S.; Gilroy, Joe B. (Synlett, 2016)
An azide-functionalized nitronyl nitroxide was synthesized and its reactivity towards the Staudinger–Bertozzi ligation was explored. Whereas a model reaction in solution showed the conversion of nitronyl nitroxide to an imino nitroxide radical, the same reaction at the interface of gold nanoparticles allowed for successful covalent incorporation of the nitronyl nitroxide radical onto the nanoparticles.
Keywords: gold nanoparticles; stable radicals; nitronyl nitroxides; bioorthogonal chemistry; EPR spectroscopy; X-ray spectroscopy